Nature of cobalt species during the in situ sulfurization of Co(Ni)Mo/Al(2)O(3) hydrodesulfurization catalysts - al Samarai, Mustafa (J Synchrotron Radiat, 2019)
The evolution in local structure and electronic properties of cobalt was investigated during in situ sulfurization. Using a combination of 1s X-ray absorption (XAS) and 1s3p resonant inelastic X-ray scattering (RIXS), the valence, coordination and symmetry of cobalt ions were tracked in two cobalt-promoted molybdenum oxide precursors of the hydrodesulfurization catalyst system, namely Co–Mo/Al(2)O(3) and Co–Ni–Mo/Al(2)O(3). Extended X-ray absorption fine structure shows that the Co—O bonds were replaced with Co—S bonds as a function of reaction temperature. The cobalt K pre-edge intensity shows that the symmetry of cobalt was modified from Co(3+) O (h) and Co(2+) O (h) to a Co(2+) ion where the inversion symmetry is broken, in agreement with a square-pyramidal site. The 1s3p RIXS data revealed the presence of an intermediate cobalt oxy-sulfide species. This species was not detected from XAS and was determined from the increased information obtained from the 1s3p RIXS data. The cobalt XAS and RIXS data show that nickel has a significant influence on the formation of the cobalt oxy-sulfide intermediate species prior to achieving the fully sulfided state at T > 400°C.